The effect of Public Health/Pediatric Obesity interventions on socioeconomic inequalities in childhood obesity: A scoping review. (29th August 2019) - Venturelli, Francesco; Ferrari, Francesca; Broccoli, Serena; Bonvicini, Laura; Mancuso, Pamela; Bargellini, Annalisa; Giorgi Rossi, Paolo
Summary: Childhood obesity has a strong social gradient. This scoping review aims to synthesize the evidence on the impact on inequalities of non‐targeted interventions to reduce the prevalence of childhood and adolescent obesity in high‐income countries. We updated a review by Hillier‐Brown, searching up to 31 December 2017 on MEDLINE, Embase, The Cochrane Library, CINAHL, and PsycINFO, with no limitations on study design. Fifty‐eight studies describing 51 interventions were included: 31 randomized clinical trials and 27 non‐randomized trials, with sample sizes from 67 to 2, 700, 880 subjects. The majority were implemented in the school setting at a community level; the others were in health services or general population setting and targeting individuals or the system. Twenty‐nine interventions proved to be effective overall; seven others had an effect only in a subgroup, while 15 proved not to be effective. All types of included interventions can increase inequalities. Moreover, some interventions had opposite effects based on the socioeconomic characteristics. Any kind of intervention can reduce equity. Consequences are difficult to predict based on intervention construct. Complex interventions acting on multiple targets, settings, and risk factors are more effective and have a lower risk of increasing inequalities.